The Association Between Hemoglobin HbA1c with Serum Inorganic Phosphate in Children with Type 1 Diabetes - Dalili S (Dove Medical Press, 2020)
Setila Dalili,1 Shahin Koohmanaee,1 Seyyed Amir Reza Nemati,1 Seyyedeh Azade Hoseini Nouri,1 Afagh Hassanzadeh Rad,1 Wesam Kooti2 1Pediatric Diseases Research Center, Guilan University of Medical Sciences, Rasht, Iran; 2Lung Diseases & Allergy Research Center, Research Institute for Health Development, Kurdistan University of Medical Sciences, Sanandaj, IranCorrespondence: Wesam Kooti; Shahin Koohmanaee Tel +989336583929Email wesamkooti@gmail.com; Koohmana@yahoo.comBackground: Diabetes mellitus is one of the most common chronic metabolic diseases in children and adolescents, which changes the cellular metabolism. Phosphorus is an essential element for metabolism. Early in the progression of diabetes, a paradoxical metabolic imbalance in inorganic phosphate (Pi) occurs that may lead to reduced high energy phosphate and tissue hypoxia. While low and high uncontrolled blood sugars can be easily recognized by clinical symptoms, low and high plasma inorganic phosphate remain unrecognizable. Therefore, we aimed to assess the association between hemoglobin A1c (HbA1c) with serum inorganic phosphate in children with type 1 diabetes.Materials and Methods: This cross-sectional study was conducted on 102 patients selected from a pediatric ward in 17th Shahrivar hospital in Rasht, North of Iran. Clinical data including age, sex, height, weight, BMI, duration of diabetes, the level of HbA1c, and phosphorus were gathered. The level of HbA1c was adjusted by age in the final analysis.Results: The mean age of samples was 9.98± 3.91 years old and 46 participants (45.1%) were male. It was found that HbA1c had a reversed and significant relationship with BMI (r=− 0.215 and P=0.03), but there was no correlation between phosphate, age, height and weight, duration of diabetes mellitus, or rate of insulin consumption with HbA1c (P> 0.05).Conclusion: The finding showed that HbA1c had a reversed relationship with BMI but there was no correlation between phosphate and HbA1c.Keywords: phosphate, diabetes mellitus, child, glycated hemoglobin A, Iran